﻿STRUGGLE FOR LIFE IN STEVEN ALLAN SPIELBERG'S WAR OF THE WORLD MOVIE (2005): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - Mulatmi, Retno (2010)
This study is aimed to show the struggle for life in War of the World movie by using individual psychological approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on individual psychological approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the War of the World movie directed by Steven Allan Spielberg release in 2005. While the secondary data sources are other materials taken from books, movie script and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, Mise en scene, cinematography, sound and editing are related to each other and form the unity into good quality of a movie. Second, based on individual psychological analysis, there is close relation between the movie production and the individual reality underlying it, such as the personality of Rachel Ferrier is influenced by her inferiority feeling to prove struggle and her fictional finalism to be a good sense and also loves her family very much. Struggle to be an achieved by sacrifice and disorder will influence human is behaviors and acts.